Anatomic, Geographic, and Taxon-Specific Relative Risks of Carbapenem Resistance in the Health Care System of the U.S. Department of Defense - Lesho, Emil (J Clin Microbiol, 2016)
Carbapenem-resistant Pseudomonas aeruginosa, Acinetobacter spp., and Enterobacteriaceae pose urgent public health threats. The differential burden, relative risks, associations with antimicrobial consumption, and temporal trends of those taxa in large, geographically diverse U.S. health systems remain under reported. Electronic records of all patients in a geographically dispersed 280-hospital managed-care system from 2005 to 2014 were reviewed. Carbapenem-resistant strains were identified based on Clinical and Laboratory Standards Institute guidelines and breakpoints. A total of 360,000 potentially carbapenem-resistant strains were identified from 14.7 million cultures (80% infecting and 20% surveillance). Isolation of bacteria overseas or isolation from the bloodstream was associated with a higher relative risks of carbapenem resistance (CR; P < 0.0001). Enterobacteriaceae were isolated 11 times more frequently than P. aeruginosa and Acinetobacter spp. However, compared to Enterobacteriaceae, the CR levels were 73-fold and 210-fold higher in P. aeruginosa and Acinetobacter spp., respectively. Significant differences in the relative risk of CR between taxa, anatomic, and geographic locations persisted after adjustment for other variables, the biggest differences occurring between taxa. Overall, CR rates increased for Enterobacteriaceae (P = 0.03) and decreased for Acinetobacter spp. and P. aeruginosa (P < 0.0001). These data provide a useful baseline for resistance trending and have implications for surveillance. Infections acquired overseas and bloodstream infections are particularly important areas for continued monitoring.